2018
DOI: 10.3892/ijmm.2018.3979
|View full text |Cite
|
Sign up to set email alerts
|

In vitro enhancement and functional characterization of neurite outgrowth by undifferentiated adipose-derived stem cells

Abstract: Adipose-derived stem cells (AScs) can easily be obtained and expanded in vitro for use in autologous cell therapy. Via their production of cytokines and neurotrophic factors, transplanted AScs provide neuroprotection, neovascularization and induction of axonal sprouting. However, the influencing mechanism of undifferentiated AScs on nerve regeneration is currently only partially understood. In the present study, undifferentiated AScs and cutaneous primary afferent dorsal root ganglion (dRG) neurons were co-cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…Studies performed by other workgroups highlighted beneficial effects of MSCs on nerve regeneration and neurite outgrowth [ 45 , 46 ]. We therefore investigated possible effects of co-cultivation with AdMSCs on growth and morphology of SDH neurons by means of immunocytochemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed by other workgroups highlighted beneficial effects of MSCs on nerve regeneration and neurite outgrowth [ 45 , 46 ]. We therefore investigated possible effects of co-cultivation with AdMSCs on growth and morphology of SDH neurons by means of immunocytochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…The use of inserts with a fine-pored, permeable membrane provides the opportunity to investigate effects of released soluble mediators by both cultures on each other without allowing direct contact [ 61 , 62 ]. Stem cells of different origins have the capacity to stimulate neurite outgrowth and, therefore, support nerve regeneration in neurons of the peripheral nervous system [ 46 , 63 , 64 ]. This effect was improved by using MSCs differentiated into a Schwann cell phenotype for primary neurons from dorsal root ganglia in vitro [ 45 ] or in an in vivo model of sciatic nerve transection [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of peripheral nerve regeneration, neurite outgrowth of DRG neurons (DRGs) is a main indicator to predict peripheral axonal regrowth after injury. de Siqueira-Santos et al [27] suggested that extending sensory fibers of DRGs in vitro might be a regenerative property for promoting functional recovery after SNI, and Bucan et al [28] Figure 5. Nobiletin increased axonal elongation 2 weeks after SNI.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of peripheral nerve regeneration, neurite outgrowth of DRG neurons (DRGs) is a main indicator to predict peripheral axonal regrowth after injury. de Siqueira-Santos et al [27] suggested that extending sensory fibers of DRGs in vitro might be a regenerative property for promoting functional recovery after SNI, and Bucan et al [28] reported that DRG neurite elongation activated by exosomes forms adipose derived mesenchymal stem cells closely involved in peripheral nerve regeneration. In the present study, nobiletin dose-dependently regulated neurite outgrowth of primary cultured DRGs after SNI and DRG neurite elongation was significantly facilitated at 50 and 100 µM of nobiletin compared to other dosages.…”
Section: Discussionmentioning
confidence: 99%
“…The adipogenic and osteogenic differentiation of ASCs were induced by treating the cells using the respective media cocktail. Approximately 1 × 10 5 cells/cm 2 (p = 3) were seeded in a culture plate and treated with adipogenic (αMEM containing 1 µM dexamethasone, 0.5 mM 1-methyl-3-isobutylxanthine, 1 ng/mL insulin, and 100 µM indomethacin) [10] and osteogenic (αMEM supplemented with 10 mM β-glycerol phosphate, 10 mM dexamethasone, and 50 µg/mL ascorbic acid) [9] media for 21 days.…”
Section: Cell Isolation and Culturementioning
confidence: 99%